2017
DOI: 10.4172/pharmaceutical-sciences.1000312
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Penetration and Bioavailability of Novel Transdermal Quercetin-loaded Ethosomal Gel

Abstract: Quercetin has been widely used to treat many diseases because of its high antioxidant activity. However, it has low oral bioavailability and penetration through the skin. The aim of this research was to enhance penetration and bioavailability of quercetin using transdermal ethosomal gel. Three ethosomal formulae, E1 (1 %), E2 (1.5 %) and E3 (2 %) with different concentration of quercetin were prepared using thin-film hydration method. Their physical properties were characterized, and then a selected ethosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…When it forms complexes with metal ions or complex ions, its bioavailability and antioxidant effect are enhanced and strengthened. In addition to quercetin complexes, newer preparations of quercetin have emerged in recent years, including nanoparticles loaded with quercetin [105,106,107], polymeric micelles of quercetin [108], quercetin-loaded mucoadhesive nanoemulsion [109], quercetin-loaded gel [110], and others [111,112]. These preparations improve the solubility and bioavailability of quercetin, which enhances its clinical efficacy and offers new drug formulations for research and development.…”
Section: Discussionmentioning
confidence: 99%
“…When it forms complexes with metal ions or complex ions, its bioavailability and antioxidant effect are enhanced and strengthened. In addition to quercetin complexes, newer preparations of quercetin have emerged in recent years, including nanoparticles loaded with quercetin [105,106,107], polymeric micelles of quercetin [108], quercetin-loaded mucoadhesive nanoemulsion [109], quercetin-loaded gel [110], and others [111,112]. These preparations improve the solubility and bioavailability of quercetin, which enhances its clinical efficacy and offers new drug formulations for research and development.…”
Section: Discussionmentioning
confidence: 99%
“…25 It is because they would have tend to repel each other, and they would not aggregate to become a larger particle. 26 The value of zeta potential for all formulations were less than -30 mV. It indicated that all formulations might have a good stability.…”
Section: S67mentioning
confidence: 84%
“…The challenge of a study that uses dosage form for transdermal delivery is to improve the penetration through the skin to act locally or systemically. For transdermal delivery, nanoemulsion 18 , nanoparticle 10 , ethosome 20 , nanostructured lipid carriers (NLC) 21 , solid lipid nanoparticle (SLN) 22 loaded quercetin (an active compound of ACE-OCE) have been developed to improve skin penetration.…”
Section: Discussionmentioning
confidence: 99%